Neuroglobin, a Novel Target for Endogenous Neuroprotection against Stroke and Neurodegenerative Disorders - Yu, Zhanyang (Molecular Diversity Preservation International (MDPI), 2012)
Brain neurons and tissues respond to sublethal injury by activating endogenous protective pathways. Recently, following the failure of a large number of clinical trials for protective strategies against stroke that aim to inhibit a specific ischemia response pathway, endogenous neuroprotection has emerged as a more promising and hopeful strategy for development of therapeutics against stroke and neurodegenerative disorders. Neuroglobin (Ngb) is an oxygen-binding globin protein that is highly and specifically expressed in brain neurons. Accumulating evidence have clearly demonstrated that Ngb is an endogenous neuroprotective molecule against hypoxic/ischemic and oxidative stress-related insults in cultured neurons and animals, as well as neurodegenerative disorders such as Alzheimer’s disease, thus any pharmacological strategy that can up-regulate endogenous Ngb expression may lead to novel therapeutics against these brain disorders. In this review, we summarize recent studies about the biological function, regulation of gene expression, and neuroprotective mechanisms of Ngb. Furthermore, strategies for identification of chemical compounds that can up-regulate endogenous Ngb expression for neuroprotection against stroke and neurodegenerative disorders are discussed.